Changes in hemodynamics during the course of surfactant therapy in patients with hormone-dependent asthma - E. A. Аkulovа; O. V. Stepаnovа; O. V. Lovаchevа; A. A. Seyliev; K. G. Shаpovаlov; O. A. Rozenberg (Туберкулез и болезни лёгких, 2019)
Non-specific hyperresponsiveness of the respiratory tract mucosa makes one of the important pathophysiological mechanisms for asthma development; it is characterized by the increased active response of the efferent system to stimuli. When this occurs, it damages the alveoli surfactant which ensures the viability of local immunity of lung tissue. Chronic respiratory failure induces changes in the cardiovascular system. The course of inhalations with a native surfactant reduces the dependence on inhalation corticosteroid.The objective of the study: to assess the effect of the course of inhalations with surfactant on the cardiovascular system in patients with hormone-dependent asthma. Materials and methods: 15 patients with asthma underwent a 70-day course of inhalation with natural surfactant based on a certain regimen (25 mg per inhalation, 21 inhalations in total) in addition to the basic therapy (inhaled corticosteroids and bronchodilators). On the 1st and 70th days of the surfactant therapy course, oscillometry was performed in order to assess macrohemodynamic parameters.Results. After the course of treatment, pulse pressure was found to increase by 26% compared to the initial level (p <0.05), the cardiac index increased by 16% (p <0.05) and the linear blood flow rate went up by 20% (p <0.05). At the same time, the pulse wave velocity decreased by 15% (p <0.05), while specific vascular resistance went down by 24% (p <0.01). This suggests that clinical remission during surfactant therapy in asthma patients is accompanied by changes in the functional state of the cardiovascular system.